What does a brain feel like? - Tan,Z; Ewen,J; Galvan,S; Forte,A; De,Momi E; Rodriguez,y Baena F; Dini,D (Journal of Chemical Education, 2020)
We present a two-part hands-on science outreach demonstration utilizing composite hydrogels to produce realistic models of the human brain. The blends of poly(vinyl alcohol) and Phytagel closely match the mechanical properties of real brain tissue under conditions representative of surgical operations. The composite hydrogel is simple to prepare, biocompatible, and nontoxic, and the required materials are widely available and inexpensive. The first part of the demonstration gives participants the opportunity to feel how soft and deformable our brains are. The second part allows students to perform a mock brain surgery on a simulated tumor. The demonstration tools are suitable for public engagement activities as well as for various student training groups. The activities encompass concepts in polymer chemistry, materials science, and biology.